Penyesuaian Penyangga Modal dan Risiko Bank-Bank di Indonesia Sebagai Respon Terhadap Potensi Krisis Keuangan di Tengah Kondisi Ketidakpastian Global - Cici Widowati (Journal Of Business, Finance, and Economics (JBFE), 2024)
This study aims to analyze the impact of capital buffer adjustment and risk adjustment on systemic risk, using a sample of 18 banks in Indonesia, from 2006 to 2020. The results of this study indicate that risk adjustment has a positive effect on systemic risk, and capital buffer adjustment has a negative effect on systemic risk. The results of this study also show that risk adjustments and capital buffer adjustments, in response to a potential financial crisis in the midst of global uncertainty, have different impacts on systemic risk depending on global conditions.